Hybrid Prepectoral Direct-to-Implant and Autologous Fat Graft Simultaneously in Immediate Breast Reconstruction: A Single Surgeon's Experience with 25 Breasts in 15 Consecutive Cases. Issue 3 (March 2022) - Gronovich, Yoav; Winder, Gilad; Maisel-Lotan, Adi; Lysy, Ido; Sela, Elad; Spiegel, Gilad; Carmon, Moshe; Hadar, Tal; Elami, Anat; Eizenman, Nirit; Binenboym, Rami
Abstract : Background: The direct-to-implant method depends on the quality of the mastectomy flaps and can be used only when the flaps are adequately perfused. Even though the method was designed to be a definitive reconstruction procedure, it has been associated with an increased likelihood that additional operative revision will be required in order to achieve the expected final cosmetic outcome. The authors describe a hybrid prepectoral direct-to-implant method that combines autologous fat grafting in the superior medial pole with immediate reconstruction. Methods: In this prospective study, 15 patients (25 reconstructed breasts) underwent simultaneous hybrid prepectoral direct-to-implant reconstruction together with autologous fat grafting performed by a single senior plastic surgeon (Y.G). Results: The mean quantity of autologous fat grafted in the superior medial aspect of the breast was 59.4 ± 12.8 cc. The mean total volume of the hybrid reconstructed breast, including implant and autologous fat graft, was 497.2 ± 89.1 cc. Satisfying final outcomes were achieved in all cases. There were no major complications, although minor complications were observed. Conclusions: The authors' hybrid approach allows the surgeon to achieve a more satisfying outcome with regard to the cleavage area. It results in a better natural appearance, an improved contour, and reduced upper pole rippling and deflation, with a lower likelihood that an additional operative revision will be required to achieve the desired final aesthetic outcome. The authors believe that their hybrid approach should be implemented as an integral part of the direct-to-implant prepectoral reconstruction procedure. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.